Preparation and Properties of Anionic nylon-6-b-Polyether Amine Copolymers with Varying Soft Chain Length. Issue 14 (22nd September 2018) - Xu, Sheng; Wang, Zhenxi; Cao, Meng; Dai, Xin; Zhang, Shangxi; Liu, Lingli
ABSTRACT: Monomer casting nylon-6- b -polyether amine (MCPA- b -PEA) copolymer were prepared through anionic polymerization which initiated by TDI-PEA macroinitiators with varying PEA molecular chain length. It was found that the TDI-PEA macroinitiator showed relatively low reactivity during the reaction process due to the long-chain PEA structure. The MCPA- b -PEA with shortest PEA chain length displayed highest crystallinity and biggest spherulites with large crystal grain size. The copolymers with long PEA chain length showed obvious toughness characteristic while that with short PEA chain length presented high tensile strength. The toughening mechanism was deduced to the combination of craze-shear band mechanism and multilayer crack extension mechanism. GRAPHICAL ABSTRACT: